2017
DOI: 10.1111/eip.12517
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation in individuals at ultra‐high risk for psychosis and its association with suspiciousness independent of depression

Abstract: The findings of the present study suggest that suspiciousness may serve as a risk indicator for suicide in clinical practice for UHR individuals. It is crucial to focus on the risk of suicide in the UHR population, as they require sufficient clinical attention and proper management for crises related to their unusual and confusing experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
19
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 50 publications
3
19
2
Order By: Relevance
“…In this regard, positive correlations were found between BDI‐II item 9 score and three main psychopathological features: (1) depression severity (both in its cognitive and somatic‐affective components), (2) some specific items of the CAARMS related to Huber's basic symptoms (BS) (i.e., subjective emotional disturbance, subjective complaints of impaired autonomic functioning, and subjective tolerance to normal stress), and (3) CAARMS factor 1 (“Negative‐interpersonal dimension”). Differently from some previous studies (Bang et al., ; Gill et al., ; Niendam et al., ), this pattern coheres with findings of a previous study (Gill et al., ), who showed higher depression severity in UHR individuals with suicidal ideation in comparison with those without suicidal ideation. Moreover, in the current study, more severe levels of depressive symptoms correctly were the single most important psychopathological factor that predicted suicidal ideation in UHR+ adolescents (75% of correct dichotomized BDI‐II item 9 ascription in the logistic regression model).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In this regard, positive correlations were found between BDI‐II item 9 score and three main psychopathological features: (1) depression severity (both in its cognitive and somatic‐affective components), (2) some specific items of the CAARMS related to Huber's basic symptoms (BS) (i.e., subjective emotional disturbance, subjective complaints of impaired autonomic functioning, and subjective tolerance to normal stress), and (3) CAARMS factor 1 (“Negative‐interpersonal dimension”). Differently from some previous studies (Bang et al., ; Gill et al., ; Niendam et al., ), this pattern coheres with findings of a previous study (Gill et al., ), who showed higher depression severity in UHR individuals with suicidal ideation in comparison with those without suicidal ideation. Moreover, in the current study, more severe levels of depressive symptoms correctly were the single most important psychopathological factor that predicted suicidal ideation in UHR+ adolescents (75% of correct dichotomized BDI‐II item 9 ascription in the logistic regression model).…”
Section: Discussionsupporting
confidence: 84%
“…Differently, Bang et al. () recently found that suicidal thinking severity in UHR subjects was significantly associated with experiences of suspiciousness, as measured in the Structured Interview for Psychosis‐risk Syndromes (SIPS) (McGlashan et al., ), independent of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations